Listing Practice in French Conversation: From Collaborative Achievement to Interactional Convergence - Roxane Bertrand; Beatrice Priego-Valverde (Discours)
Listing practice is an activity requiring a multi-unit turn produced by one single speaker. In this article, and following previous works within the conversation analysis framework, we will focus on lists elaborated by two participants, thus, describing lists as a “collaborative achievement”. In a first time, we will present the relevant features which make list construction a good candidate for illustrating such a collaborative achievement. But in a second time, we will investigate to what extent this collaborative achievement can be considered a true interactional convergent construction. Using a sequential and qualitative analysis, we investigate lists in a French conversational corpus. In a two-step analysis, we will first extract a list item provided by recipient within list. This item, considered a specific feedback response (Bavelas et al., 2000) illustrates the active collaboration from the recipient. In Stivers’ term (2008), this specific feedback aligns and affiliates with prior turn. Secondly, we will show that, depending on how the speaker orients to the feedback, this latter can be more or less accepted, hence, the hearer’s collaboration to the construction of the list. Thus, this work enables to confirm the proactive nature of feedback (Tolins & Fox Tree, 2014). Moreover, this would provide new insights into interactional convergence that cannot be reduced to a collaborative achievement.